Effect of Nitrogen Atoms Number and Spatial Location on Tribological Properties of Nucleobase Derivatives - Zhang, Haobo; Xia, Yanqiu; Liu, Xiong; Li, Jindu; Fan, Xiaoqiang (Tribology letters, 2016)
Four kinds of ashless, non-phosphorus and non-sulfur oil-soluble compounds of nucleobase derivatives were evaluated as lubricant additives in poly(ethylene glycol) (PEG) for steel–steel contact under room temperature, and their electrochemical corrosion behaviors were measured by Tafel polarization. The morphologies and chemical features of the worn surfaces were investigated by scanning electron microscope and X-ray photoelectron spectroscopy (XPS). The results showed that the nucleobase derivatives as 2 wt% additive show excellent load-carrying capacity, friction-reducing and anti-wear performance. It is also found that the tribological performance of the two purine derivatives is better than that of the two pyridine derivatives. The corrosion behaviors of four PEGs with 2 wt% different nucleobase derivative additives on pure coppers exhibit much better than those of pure PEG. The XPS results indicated the excellent tribological properties are attributed to the formation of tribochemical adsorption and chemical reaction films on the worn surfaces, which may prevent the sliding surfaces from straight asperity contact and markedly improve friction-reducing and anti-wear behaviors.